The role of learning in the development and use of maritime technology in the Mediterranean 1500 BC to AD 200 - Ross, Keith (2025)
The evidence available to the discipline of maritime archaeology, and the associated interpretation of textual and iconographic sources, has recently undergone a period of rapid growth due to the development of techniques used in underwater exploration. Unfortunately, the presentation and interpretation of this expanded evidence has neither a clear taxonomic structure within which to categorise vessels by type and capability, nor a comprehensive model for development that might explain how, why and when different vessel types arose. The result has been that most published works by specialists in the field do not clearly reference either topic. This in turn has resulted in a great deal of misunderstanding by scholars from outside the discipline regarding vessel types, capabilities and usage. My contention in this thesis is that an understanding of the nature of learning in the ancient world can provide a means to explain how the process of vessel development progressed. Any process of development based on learning will clearly be linked to both the construction and operation of the vessels in use. This in turn requires the definition of vessel types in the form of a system of taxonomy based on features related to their use. The aim and objectives of this thesis are to provide a model of this process of learning and system of taxonomy that fits the current evidence, while providing a basis of challenge for others researching in the field of maritime archaeology.